The Influence of Product Quality, Perceived Price, and Promotion on Purchase Decisions for Citra Brand Shower Soap in Kudus (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research aims to examine the impact of product quality,perceived price , and promotional strategies on the purchasing decisions of consumers of Citra brand bath soap in Kudus City. The study is motivated by the brand’s recent decline in the Top Brand Index, attributed to heightened market competition and shifting consumer preferences. Employing a quantitative method with an explanatory research design, the study surveyed 100 respondents who use Citra bath soap in Kudus, selected through purposive sampling. Data collection was carried out via questionnaires and analyzed using multiple linear regression. The findings reveal that product quality, price, and promotion each exert a positive and significant influence on consumer purchasing decisions. These results suggest that, in order to remain competitive and foster customer loyalty, businesses should focus on enhancing product quality, establishing fair pricing, and executing targeted and impactful promotional efforts.
Keywords: Product Quality; Perceived price; Promotion; Purchasing Decision